Tourism Sustainability Strategy Analysis of the Lembung Pamekasan Mangrove Ecotourism Object Using the Analytic Network Process Approach - Zaini, Moh.; Sutikno; Anita Kristina (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This research uses the Analytic Network Process approach to analyze the priority of tourism sustainability strategies for the Pamekasan Lembung Mangrove Ecotourism object. The quantitative research approach with the ANP Super Decisions method is used to analyze the complexity of the problems of economic aspects, social aspects, environmental aspects, infrastructure aspects, and institutional aspects by measuring the priority level based on the ratio value, primary data obtained directly from expert respondents, academic experts, regulatory experts and practitioners. The results show that to create tourism sustainability; the most appropriate development strategy is the strategy of increasing the value of capital, investment and promotion with the highest priority value of 35%, as a solution to the problem of capital and tourist visits and focusing on economic aspects with a priority level of 27.9%, with implications for policy recommendations for the government in preparing regional development planning, especially for sustainable tourism development.